2005
DOI: 10.1080/10668920590524238
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development Needs of Full-Time Faculty in Technical Colleges

Abstract: In the Georgia technicd college system, 714 full-time faculty members rated the importance of various areas of professional development. The developmental activities fell into the clusters of technology, student guidance and support, instruction, promotion. administration and management, and curriculum. The highest rated item in the technology cluster was the ability to use email. ranked seventh overall. In student support and guidance. providing academic advising was ranked fifth overall. The instructional cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 3 publications
1
29
0
1
Order By: Relevance
“…McGregor (2002) took this belief even further and claimed that ''positive change in pedagogy comes through a sustained faculty development program that focuses on learning outcomes'' (p. 724). Wallin and Smith (2005) found that faculty want focused activities that help them not only develop their instructional techniques, but that are also well-planned, goal-oriented, and supportive.…”
Section: Iowa Central Community College Fort Dodge Iowa Usamentioning
confidence: 97%
See 1 more Smart Citation
“…McGregor (2002) took this belief even further and claimed that ''positive change in pedagogy comes through a sustained faculty development program that focuses on learning outcomes'' (p. 724). Wallin and Smith (2005) found that faculty want focused activities that help them not only develop their instructional techniques, but that are also well-planned, goal-oriented, and supportive.…”
Section: Iowa Central Community College Fort Dodge Iowa Usamentioning
confidence: 97%
“…VanDerLinden (2005) wrote about faculty development in terms of professional development which included, ''furthering one's education, participating in professional development activities, and cultivating mentoring relationships'' (p. 729). Wallin and Smith (2005) suggest that professional development should be relevant to teachers with a goal of offering innovative ways to keep teaching methods and delivery fresh. According to Newland, Newland, Steele, Lough, and McCurdy (2003), the goal of faculty development is to provide all faculty members with developmental resources for meaningful and productive careers.…”
Section: Iowa Central Community College Fort Dodge Iowa Usamentioning
confidence: 98%
“…Organizuojant tyrimą pirmiausia orientuotasi į tuos veiklos aspektus, kurie turėtų būti svarbūs Lietuvos aukštųjų mokyklų dėstytojams. Tuo tikslu tyrėjai rėmėsi mokslinių šaltinių analize, o žinias ir gebėjimus sugrupavo pagal dėstytojo veiklos sritis, kurias numatė D. L. Wallin ir C. L. Smith (2005) Tyrimo, vykdyto 2015 m., metu prašyta skirtingų šalies miestų aukštųjų mokyklų dėstytojų įvertinti nurodytų žinių ir gebėjimų trūkumą bei pažymėti kai kuriuos demografinius duomenis: lytį, pedagoginio darbo aukštojoje mokykloje stažą, mokslinių tyrimų sritis, aukštosios mokyklos tipą, mokslo laipsnį. Šioje anketoje respondentų prašyta nurodyti pagal keturbalę ranginę skalę, kaip stipriai jie įsisąmonina nurodytų žinių ir gebėjimų trūkumą.…”
Section: Tyrimo Metodai Imtis Ir Organizavimasunclassified
“…The research indicates that faculty members need to be provided with more information on how to integrate the newest forms of technology in their classroom and faculty development activities could drive the delivery of this information. As stated by Wallin and Smith (2005). "…the changing demands of employers and emerging technologies place additional stress on faculty" (p. 88).…”
Section: Activities and Concernsmentioning
confidence: 99%